Navigating the Iron Triangle: A Systematic Mixed-Methods Review of Equity and Quality Trade-offs in Indonesia’s National Health Insurance Reform - Sutrisni; Anggara Setya Saputra; Indi Nurul Anisah; Arinda Retno Setiani; Fika Meiliana Saputri (HM Publisher, 2025)
As Indonesia’s Jaminan Kesehatan Nasional (JKN) transitions from an expansionary phase to maturity, it faces the classic iron triangle of health policy: the tension between expanding access, containing costs, and maintaining quality. While coverage rates have soared, critical questions remain regarding the equitable distribution of these benefits in a post-pandemic landscape. This study employs an Integrative Systematic Review design, synthesizing high-impact quantitative and qualitative evidence published between 2021 and 2024. Data were extracted from six primary studies utilizing large-scale national datasets (SUSENAS, IFLS) and policy reviews. The analysis moves beyond simple pooling to perform a narrative synthesis of adjusted Odds Ratios (aOR) for utilization and benefit incidence, assessing the structural determinants of effective coverage. The synthesis reveals a distinct inverse equity trade-off. While JKN ownership significantly increases the probability of inpatient utilization (aOR: 2.35), the benefits are unevenly distributed. A middle-class capture phenomenon is evident, where upper-middle-income groups experience a 41% reduction in out-of-pocket (OOP) expenditure compared to 38% for the poorest quintile. Furthermore, a quality gap persists, with non-poor populations seeing a greater reduction in unmet needs (10.4%) than the poor (7.7%), largely driven by supply-side rigidities in remote areas and administrative literacy barriers. In conclusion, JKN has successfully dismantled financial entry barriers but has not yet resolved structural inequities. The system currently functions as a regressive subsidy where the urban middle class extracts disproportionate value. Future policy must pivot from coverage expansion to supply-side equity, implementing geographic capitation differentials and targeted non-medical benefits for vulnerable populations to close the gap between legal entitlement and effective access.